2012
DOI: 10.1021/ic202709x
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV) Complexes of Disulfide-Linked Schiff Bases

Abstract: With the goal of preparing Ti(IV) complexes bearing a sulfur-based redox function of possible use in electrocatalytic oxidations of alcohols at electrode surfaces, a series of seven 2,2'-dithiodianiline Schiff-base derivatives, including two new variations, were tested in reactions with Ti(OR)(4) (R = (i)Pr, (t)Bu). Instead of the expected dimetallic products of general formula [LTi(OR)(2)](2), mononuclear species LTi(OR)(2) were obtained, confirmed by crystallographic determinations to have an unprecedented, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the absence of an additionally coordinating substituent the salicyclaldiminate-substituted derivatives [M(OR) 2 (SA) 2 ] (M=Zr, Ti; SA=salicylaldiminate) have the same geometry as the corresponding complexes [M(OR) 2 (β-diketonate) 2 ], that is, with the OR groups in positions cis to each other 4. This structural motif was also found in a complex in which the two SA ligands are connected through a C 6 H 4 –S–S–C 6 H 4 bridge (Scheme 1, bottom left)5 as well as in the hydrolyzed compound [{(salen)TiO} 2 ] (salen= N , N ′-ethylenebis(salicylimine)), in which the two Ti atoms are bridged by two oxo groups 6. Recently Tzubery et al reported the monomeric compound [Ti(salen)(OC 6 H 3 Me 2 ) 2 ] with the aryloxo ligands in positions trans to each other 7…”
Section: Introductionmentioning
confidence: 70%
“…In the absence of an additionally coordinating substituent the salicyclaldiminate-substituted derivatives [M(OR) 2 (SA) 2 ] (M=Zr, Ti; SA=salicylaldiminate) have the same geometry as the corresponding complexes [M(OR) 2 (β-diketonate) 2 ], that is, with the OR groups in positions cis to each other 4. This structural motif was also found in a complex in which the two SA ligands are connected through a C 6 H 4 –S–S–C 6 H 4 bridge (Scheme 1, bottom left)5 as well as in the hydrolyzed compound [{(salen)TiO} 2 ] (salen= N , N ′-ethylenebis(salicylimine)), in which the two Ti atoms are bridged by two oxo groups 6. Recently Tzubery et al reported the monomeric compound [Ti(salen)(OC 6 H 3 Me 2 ) 2 ] with the aryloxo ligands in positions trans to each other 7…”
Section: Introductionmentioning
confidence: 70%
“…Also in a disulfide-linked Schiff base prepared by Donzelli et al, a value of 2.064 (2) Å is reported for a similar bond [45]. The C10-S2 and C11-S3 bond distances are 1.742 (8) Å and 1.757 (7) Å, and the lengths of two C7-N2 and C14-N5 imine bonds are 1.281 (11) Å and 1.296 (10) Å.…”
Section: Crystal Structurementioning
confidence: 83%
“…Multivalent Schiff base ligands ( Figure 2 ) eagerly form complexes: bidentate and tridentate with Co(II), Ni(II) ions, as well as four-dentate, highly stabilizing metal ions at various oxidation states, starting with divalent Ni(II), Cu(II), Pd(II) or tetravalent V(IV), Ti(IV), up to uranium U(III,IV,V) [ 10 , 11 ]. The donor atoms (O, N, S) of bidentate ligands can occur, for example, in ON or NN sequences, tridentate ligands—ONO, NNN or ONS or NNS (where the sulfur atom comes from, for example, disulfide bridges) and in tetradentate ligands—NNNN, ONNO, NSNO [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%